2000
DOI: 10.1074/jbc.m000296200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Recombinant IKK1/IKK2 Heterodimer

Abstract: Nuclear factor kappa B (NF-B) is a ubiquitous, inducible transcription factor that regulates the initiation and progression of immune and inflammatory stress responses. NF-B activation depends on phosphorylation and degradation of its inhibitor protein, IB, initiated by an IB kinase (IKK) complex. This IKK complex includes a catalytic heterodimer composed of IB kinase 1 (IKK1) and IB kinase 2 (IKK2) as well as a regulatory adaptor subunit, NF-B essential modulator. To better understand the role of IKKs in NF-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 33 publications
4
60
1
Order By: Relevance
“…Binding of ␥-35 S-ATP also occurred only with the active, phosphorylated form of rhIKK-2. We have shown previously that the rhIKK-2 expressed in a baculovirus system is phosphorylated and active (36,37). As demonstrated previously, phosphatase-treated rhIKK-2 had no kinase activity, and Western blot analysis confirmed that equal amounts of rhIKK-2 were immunoprecipitated and assayed (Fig.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…Binding of ␥-35 S-ATP also occurred only with the active, phosphorylated form of rhIKK-2. We have shown previously that the rhIKK-2 expressed in a baculovirus system is phosphorylated and active (36,37). As demonstrated previously, phosphatase-treated rhIKK-2 had no kinase activity, and Western blot analysis confirmed that equal amounts of rhIKK-2 were immunoprecipitated and assayed (Fig.…”
Section: Resultsmentioning
confidence: 58%
“…Antibody complexes were pelleted by centrifugation and washed 3 times with 1 ml of cold whole-cell lysis buffer followed by 2 washes in kinase buffer (25 mM HEPES, pH 7.6, 2 mM MgCl 2 , 2 mM MnCl 2 , 10 mM NaF, 5 mM DTT, and 1 mM phenylmethylsulfonyl fluoride). 100 -200 g of immunoprecipitated IKK was analyzed for kinase activity in a reaction containing 10 M biotinylated I B␣ peptide as substrate and 1 M [␥-33 P]ATP (2500 Ci/mmol) as described previously (36,37). After incubation at room temperature for 30 min, 25 l of the reaction mixture was withdrawn and added to a SAM TM 96 biotin capture plate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, ADP has been shown to be a competitive inhibitor with respect to the ATP substrate (24), and the peptide inhibitor is a competitive inhibitor with respect to peptide substrate (20). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…First, because IKK␤ and IKK␣ are in the same high-molecular-weight complex in the cytoplasm, it is conceivable that by inhibiting the ability of IKK␤ to phosphorylate I B␣, I B␣ may be more available to IKK␣ as a substrate. In this regard, it is notable that IKK␣ is considerably less active than IKK␤ as an I B␣ kinase in vitro (33), and thus if I B␣ is brought in proximity to the IKK␣␤␥ complex during cellular signaling, it may be preferentially phosphorylated by IKK␤. During antigen receptor stimulation, BCL10 is an additional substrate of IKK␤ (34,35).…”
Section: Discussionmentioning
confidence: 99%